Mental health care in modern England : the Norfolk Lunatic Asylum/St. Andrew's Hospital c. 1810-1998 - Cherry, Steven (Boydell Press, 2003)
The Norfolk Lunatic Asylum opened in 1814 as a pioneer county pauper institution and in 1998 St Andrew's featured among the last of the large psychiatric hospital closures. This history of one particular place for 'madness' covers changing approaches to insanity and treatments over two centuries.